2009
DOI: 10.1378/chest.08-2776
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Is Common in Idiopathic Pulmonary Fibrosis

Abstract: Results: Fifty subjects enrolled and completed a NPSG. The mean age was 64.9 years, and the mean BMI was 32.3. OSA was diagnosed in 88% of subjects. Ten subjects (20%) had mild OSA (AHI, 5 to 15 events per hour), and 34 subjects (68%) had moderate-to-severe OSA (AHI, > 15 events per hour). Only 6 subjects (12%) had a normal AHI. One patient was asymptomatic as determined by ESS and SA-SDQ, but had an AHI of 24 events per hour. The sensitivity of the ESS was 75% with a specificity of 15%, whereas the SA-SDQ had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
221
4
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(289 citation statements)
references
References 29 publications
29
221
4
26
Order By: Relevance
“…1,12 Nevertheless, it should be noted that 90% of individuals with sleep apnea are undiagnosed. 21 The prevalence of habitual snoring was similar to findings from studies conducted in the USA (46%) and Malaysia (47.3%). 5,20 The prevalence observed in our study was higher than in the following other regions: Nigeria 31.6%, 10 São Paulo 31% 22 and France 22%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1,12 Nevertheless, it should be noted that 90% of individuals with sleep apnea are undiagnosed. 21 The prevalence of habitual snoring was similar to findings from studies conducted in the USA (46%) and Malaysia (47.3%). 5,20 The prevalence observed in our study was higher than in the following other regions: Nigeria 31.6%, 10 São Paulo 31% 22 and France 22%.…”
Section: Discussionsupporting
confidence: 84%
“…and also in Nigeria, India, and Hong Kong. 9,10 Epidemiological studies have confirmed that the gender ratio of OSAS is 2 to 3.1, 10,20,21 and this ratio was 1.42 in our study. In addition to cases of more prevalent OSAS disorders among men, these differences were statistically significant in our study and some other studies 1,2,4,8,23 although a study conducted in Iran did not reach any significant variation.…”
Section: Discussionsupporting
confidence: 80%
“…Prior polysomnographic studies in the mid-1980s demonstrated alterations in sleep architecture and oxygen desaturation, especially during REM sleep, but not OSA, even in morbidly obese patients with ILDs [3,4]. The results of the study by Pihtili et al related to IPF patients are similar to recent studies that report increased incidence of OSA and pointed the need for high clinical suspicion for possible underlying OSA in this population [5][6][7][8]. Prior studies dating back 10-20 years probably underestimated hypopneas by using only thermal sensors and not nasal pressure transducers which are recognized as the sensitive devices for hypopnea detection that represents the majority of the observed respiratory events in IPF patients based on the newer studies.…”
supporting
confidence: 65%
“…Secondly, much remains to be learned about the relative contribution of tobacco smoking, genetic predisposition, cardiovascular disease or risk factors, and IPF. For example, the relative risk of developing acute coronary syndrome or deep vein thrombosis is increased in IPF [6], as may be the risk of obstructive sleep apnoea [7].…”
Section: Current Challenges In Ipfmentioning
confidence: 99%